ANALISIS KEMAMPUAN PEMECAHAN MASALAH STATISTIKA SISWA DI KELAS VIII SMP NEGERI 6 PONTIANAK - Aprilia Dwi Lestari; Agung Hartoyo; Dede Suratman (Universitas Tanjungpura, 2020)
AbstractThis study aimed to determine the statistical problem-solving abilities of students in Pontianak. The type of research used is descriptive research. The subjects research in this study were 9 grade VIII students in the even semester of the 2019/2020 school year. The object of this research is the Student’s ability to solve problem in statistical material. The data obtained was analyzed according to problem solving indicators. Based on data analysis it can be conclude that 1. The research subjects had been succeeded in finding mathematical concepts that come from contextual problems and then use these concepts to solve problems. 2. The research subjects had not been able to solve problems using more than one strategies. 3. The research subjects had not been able in checking the correctness of the answer. From the three indicators, only the first indicator that the students can fulfill, namely solving problems in mathematics and other contexts. In the second indicator, students had not been able to apply and adapt various problem solving strategies. In the third indicator, students had not been able to reflect on problem solving. Keywords: Problem Solving, Statistical